2010
DOI: 10.1074/mcp.m110.000240
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Proteomics and Genomics Analysis Reveals a Novel Mesenchymal to Epithelial Reverting Transition in Leiomyosarcoma through Regulation of Slug

Abstract: Leiomyosarcoma is one of the most common mesenchymal tumors. Proteomics profiling analysis by reversephase protein lysate array surprisingly revealed that expression of the epithelial marker E-cadherin (encoded by CDH1) was significantly elevated in a subset of leiomyosarcomas. In contrast, E-cadherin was rarely expressed in the gastrointestinal stromal tumors, another major mesenchymal tumor type. We further sought to 1) validate this finding, 2) determine whether there is a mesenchymal to epithelial revertin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…Moreover, 2 noncoding RNAs involved in the regulation of EZH2, H19, and HOTAIR (39-41) turned out to be among the RNAs most significantly upregulated in FS-DFSP. This finding suggests that overexpression of H19 and HOTAIR, together with let-7 downregulation, all concur to induce EZH2 and, in turn, chromatin remodeling and mesenchymal transdifferentiation in FS-DFSP (19,(39)(40)(41). A role for epigenetic reprogramming in fibrosarcomatous transformation was also supported by the finding that 66 genes enriched in FS-DFSP versus DFSP are reported to undergo epigenetic regulation (11), and recent evidence is consistent with the involvement of chromatin remodeling in translocation-associated sarcomas (42).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Moreover, 2 noncoding RNAs involved in the regulation of EZH2, H19, and HOTAIR (39-41) turned out to be among the RNAs most significantly upregulated in FS-DFSP. This finding suggests that overexpression of H19 and HOTAIR, together with let-7 downregulation, all concur to induce EZH2 and, in turn, chromatin remodeling and mesenchymal transdifferentiation in FS-DFSP (19,(39)(40)(41). A role for epigenetic reprogramming in fibrosarcomatous transformation was also supported by the finding that 66 genes enriched in FS-DFSP versus DFSP are reported to undergo epigenetic regulation (11), and recent evidence is consistent with the involvement of chromatin remodeling in translocation-associated sarcomas (42).…”
Section: Discussionsupporting
confidence: 66%
“…In particular, the switch from DFSP to FS-DFSP was paralleled by an enrichment in genes belonging to the EMT gene signature, as defined by Gr€ oger and colleagues (15). The EMT program has been linked to aggressive tumor behavior, and modulation of mesenchymal traits toward a more undifferentiated state has been previously reported to play a pivotal role in sarcoma development and progression (16)(17)(18)(19)(20)(21). EMT is governed by a set of transcription factors, including TWIST1, SNAI2/SLUG, and ZEB1.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, Vuoriluoto and colleagues previously demonstrated that Slug induces vimentin expression and migration in mammary cells (26). Vimentin, cell invasion, and migration were also found regulated by exogenous modulation of Slug in a leiomyosarcoma cell line (27).…”
Section: Discussionmentioning
confidence: 99%
“…Several sarcomas are well differentiated and closely resemble what is thought to be the cell of origin (but could also be aberrantly differentiated), whereas others are poorly differentiated and the cell of origin remains uncertain. 8 A diverse group of sarcomas display features reminiscent of an EMT-MET, [9][10][11][12] suggesting that sarcomas may have some phenotypic plasticity.…”
Section: Introductionmentioning
confidence: 99%